Reviewer Acknowledgements and Highlights: Equity, Resilience, and the Human Dimensions of Health – GHMJ (Global Health Management Journal), Volume 9, Number 2, 2026 - GHMJ (Global Health Management Journal) (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
The Editorial Board gratefully acknowledges the reviewers who contributed their time, expertise, and careful judgment to the manuscripts published in the issue of the Global Health Management Journal (Vol. 9, No. 2, 2026). Many of the contributions in this issue share a common concern with the conditions that shape health opportunities and outcomes. Kpum and Gasa (2026) challenge educational systems to recognize the financial and safety realities faced by women learners, while Mboma et al. (2026) draw attention to the vulnerabilities experienced by street-connected children in Kinshasa. Beyond individual experiences, Ali and Makoni (2026) demonstrate how climate variability can intensify financial hardship and worsen health outcomes among households affected by non-communicable diseases, reinforcing the need for policies that respond to both social and environmental challenges. Looking ahead, Peter and Gasa (2026) highlight the potential of entrepreneurship, innovative education, and cross-sector collaboration in building more sustainable and resilient health systems. The recently completed publications from Faculty of Medicine, Universitas Swadaya Gunung Jati, processed under Special Edition commitment, represent new insights from biomedical and educational research. Genetic studies by Rizqulloh et al. (2026) and Soeroso et al. (2026) explore biological factors associated with diabetes and malaria, offering insights that may guide future research and disease prevention efforts. Within medical education, Maharani et al. (2026) examine the attributes of lecturers facilitating problem-based learning, emphasizing the continuing importance of student-centered approaches in preparing future health professionals. Completing the issue, Sanitaquin et al. (2026) explore cardiovascular endurance and blood pressure among university employees, adding to the ongoing conversation on lifestyle, health, and disease prevention. Together, the articles in this issue remind us that improving health requires not only scientific advances, but also a deeper understanding of the social, educational, economic, and environmental realities in which people live. We are grateful for the Editorial Boards and Reviewers’ commitment to advancing global health research and supporting a rigorous peer-review process. Link to download: https://publications.inschool.id/index.php/ghmj/issue/view/GHMJ.09.02 Editor-in-chief Prof. Andrew John Macnab Managing Editors Doni Marisi Sinaga, M.Sc. Kukuh Madyaningrana, M.Biotech. Ph.D. Journal Managers Suyitno, M.PHM Maretalinia, M.A External Reviewers Dr. Jude Ali Igyo (Mewar International University, Nigeria) Dr. Agi Christiana Ikpoyi (Joseph Sarwuan Tarka University, Nigeria) dr. Ratih Yulistika Utami, MMedEd (Universitas Muhammadiyah Sumatera Utara, Indonesia) Donny Nauphar, M.Si.Med. (Universitas Swadaya Gunung Jati, Indonesia) dr. Ike Sulistyowati, M.Biomed., Sp.Rad. (Universitas Bengkulu, Indonesia) drg. Musri Amurwaningsih, MMedEd (Universitas Islam Sultan Agung, Indonesia) dr. Ziske Maritska, M.Si.Med (Universitas Sriwijaya, Indonesia) dr. Siti Farhanah Aulia, M.Biomed (Universitas Yarsi, Indonesia) Emmanuel Aondongusha Asue, Ph.D (University of South Africa, South Africa) Dr. Isaac Msughter Peter (University of South Africa, South Africa) Rodrigue Nakasala, MD, MSc., MPH. (SANRU Asbl, Democratic Republic of the Congo) Dr. Tersoo Solomon Shaminja (Rev. Fr. Moses Orshio Adasu University, Nigeria) Dr. Fekumo Bolouembeledo (Federal University Otuoke, Nigeria) In recognition of their service, eligible reviewers may submit one Perspective or Guest Editorial article annually to a Special Edition free of publication charges. We further welcome collaboration with reviewers interested in contributing as members of our Editorial Board. Acceptance Rate : 25 % Days to First Editorial Decision : 22 days Days to accept : 35 days Published: 03 June 2026.